Renovation of industrial areas in the structure of rural settlements (on the example of the ceramic factory in the village of Nizhnie Tavolgi) - M. Yu. Gaydouk; A. S. Holmanskikh (Vestnik MGSU)
Introduction. Renovation of preserved historical industrial territories is of great importance both for the development of rural settlements and regions as a whole, where a large number of currently underutilized and abandoned enterprises of the period of XIX – early XX centuries have been preserved. The main objective of this study is to present an example of a comprehensive approach to the issue of territory renovation, including all the main stages from pre-project and design analysis to the development of a project proposal.Materials and methods. The study of the design territory and objects is based on a comprehensive approach, including the analysis and use of Soviet and modern archival and bibliographic sources; collection and processing of documents, graphic and photographic materials, results of field survey (photo-fixation, measurements); systematization of research results.Results. The expediency of preservation and practical use of industrial enterprises is illustrated on the example of the developed project proposal for the renovation of the ceramic factory complex in the village of Nizhnie Tavolgi, Sverdlovsk region. The research materials present the prospects of their functional renewal and renovation in the modern conditions of rural settlements development.Conclusions. The research, popularization of significant objects that form the architectural appearance of settlements and their inclusion in modern realities is an important and necessary process both for the creation of a diverse quality environment, formation of place identity and education in the field of national history and culture.